Design of nonlinear predictive generalized minimum variance control for performance monitoring of nonlinear control systems. (October 2021) - Sheikhi, Mohammad Amin; Khaki-Sedigh, Ali; Nikoofard, Amirhossein
Abstract: In this paper, a nonlinear predictive generalized minimum variance (NPGMV) controller is proposed and explicitly formulated for a class of nonlinear systems modeled by autoregressive second-order Volterra series, applying the polynomial approach. Hence, a new benchmark controller for performance assessment is introduced to improve the achievable control performance. Furthermore, to have an efficient control assessment, a data-driven algorithm based on the NPGMV control is presented that uses only the closed-loop operating data. In the design procedure, a multi-step cost function is defined to incorporate predictive action. Exploiting the predictive control concept enables the control scheme to handle constrained problems. Also, the proposed control algorithm utilizes an inherent integrating effect, which is essential for practical purposes. Volterra series are employed for modeling and identification of the nonlinear processes, using conventional least-squares methods. To show the effectiveness of the proposed methodology, simulation results and comparison studies are provided on a cascade Wiener model and a continuous stirred tank reactor (CSTR) chemical pilot plant. Finally, an experimental study on a pressure pilot plant is used to demonstrate the applicability of the proposed control scheme. The simulation and experimental results indicate satisfactory performance of the proposed controller. Highlights: Design of a nonlinear predictive generalized minimum variance (NPGMV) control. A second-order Volterra structure is used in the control scheme. A data-driven approach is presented to estimate the NPGMV performance index. The proposed method enables the control scheme to handle constrained problems. Simulation and experimental results evaluate efficiency of the proposed methods.